Middle to Late Jurassic palaeoclimatic and palaeoceanographic trends in the Euro-Boreal region: Geochemical insights from East Greenland belemnites - Vickers, Madeleine L.; Hougård, Iben W.; Alsen, Peter; Ullmann, Clemens V.; Jelby, Mads E.; Bedington, Michael; Korte, Christoph (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
Supplementary data and code for Vickers, M.L., Hougård, I.W., Alsen, P., Ullmann, C.V., Jelby, M.E., Bedington, M. and Korte, C., 2022. Middle to Late Jurassic palaeoclimatic and palaeoceanographic trends in the Euro-Boreal region: Geochemical insights from East Greenland belemnites. Palaeogeography, Palaeoclimatology, Palaeoecology , 597 , p.111014.